Effective Improvement of Thermodynamics and Kinetics of BiVO4 Photoanode via CuI for Photoelectrochemical Water Oxidation - Guan, Yuan (Langmuir : the ACS journal of surfaces and colloids, 2024)
The preparation of durable and efficient photoanodes for photoelectrochemical water oxidation is of great importance in promoting the development of green hydrogen production and artificial photosynthesis. Here, n-type BiVO4 was combined with p-type CuI to construct a CuI/BiVO4 (CIB-1) p-n heterojunction photoanode. The composite photoanode effectively overcame the drawbacks of BiVO4, such as low separation and injection efficiency of photogenerated electron-hole pairs. As a result, the CIB-1 had the highest photocurrent density of 1.98 mA cm-2, which was 2.5 times higher than pure BiVO4 with 0.79 mA cm-2 at 1.23 V (vs RHE) under AM 1.5G light irradiation. The CIB-1 had a lower Tafel slope of 23.2 mV decade-1 compared to 47.9 mV decade-1 for BiVO4, so the water oxidation kinetics was remarkably advanced over CuI/BiVO4. Based on DFT calculations, the OER overpotential of 0.480 V for CuI/BiVO4 was significantly lower than that of 1.546 V for BiVO4 due to the lower free energy from OH- to oxygen over CuI/BiVO4 compared to BiVO4